THE EFFECT OF POWDERED NONI FRUIT (Morinda citrifolia) AS A FEED SUPPLEMENT ON THE GROWTH AND SURVIVAL RATE OF SILVER BARB (Barbonymus gonionotus) - Putri, Mutiara; Hidayati, Sri; Armando, Eric (Asian Journal of Aquatic Sciences, 2024)
Silver barb is one of the fish that can be cultivated year-round due to their excellent ability to adapt to Indonesian climate. One of the problems that cultivators often face is feeding; long-term commercial feeding or pelleting will negatively impact the fish’s body. Therefore, a natural admixture of feed can become an alternative solution. This study used powdered noni fruit as a feed supplement for silver barb (Barbonymus gonionotus) because of its content of antioxidant compounds that can reduce oxidative stress due to free radicals. This study aims to determine the best practice of feeding powdered noni fruit as a feed supplement and its influences on silver barb's growth and survival rate during the fingerling phase. The study was conducted in November – December 2022 using a complete randomized design experiment consisting of four treatments and four retries. Random sampling took five fish sized 2 – 3 cm as samples. The cultivation container used in this study has a volume of 30 L, with each container containing ten samples. This study uses one-way ANOVA and is continued with a DMRT test to find the best doses of powdered noni fruit. The result shows that the best addition of noni powder was 15% of the total feed. This addition of noni powder demonstrates an increase of growth yield by 1.62 cm, absolute weight of 2.11 g, 87.5% survival rate, and feed conversion ratio of 0.0535. Moreover, the percentage of fish weight increases by 1.1% for every 1% increase in height